Potret Empiris Kinerja Keuangan Perbankan Syariah Di Indonesia: Systematic Literature Review - Fatmariyah, Fatimatul; Samsuri, Andriani; Yazid, Muhammad; AS, Fathor (Jurnal Ilmiah Ekonomi Islam, 2022)
The purpose of this study was to identify the financial performance of Islamic banking whose data were obtained from journals in the period 2017-2021 and how the solution was with a systematic literature review method approach. The results of a systematic literature review show that, 1). The distribution rate of articles in 2017 was 11, in 2018 there were 6, in 2019 there were 7, in 2020 there were 5 and in 2021 there were 2 articles in 31 journals, 2). The research method used by the researchers is a descriptive quantitative approach with a descriptive statistical approach and none uses a qualitative approach or mix methods, 3). The types of performance measurement tools used are mostly financial ratios, 4). The portrait of Islamic banking financial performance is volatile and tends to improve, 5). The solution for Islamic banks is to improve the performance of their financial ratios, and 6). The limitations of the study lie in the number of samples, variables and indicators, period of observation, and analytical techniques.